Spiritus Eschaton: Reflections on the Presence of the Holy Spirit as the Guarantee and Fulfillment of God's Plan for the End of Time - Karundeng, Ruddy Yanny; Ignatius, Yossy Francsiskus; Abraham, Jessica Elizabeth; Sanjaya, Yusak (PT FORMOSA CENDEKIA GLOBAL, 2025)
This paper examines the theological role of the Holy Spirit as Spiritus Eschaton—the Spirit who guarantees, seals, and fulfills God’s plan of salvation—in response to renewed eschatological debates sparked by the viral “rapture” rumor of September 2025. Using theological hermeneutics and historical analysis of biblical Greek and Hebrew texts, as well as early church traditions, the study explores the concept of arrabōn tou pneumatos (“the guarantee of the Spirit”) in Ephesians 1:13–14 and 2 Corinthians 1:22. It finds that the Holy Spirit serves as tangible proof of believers living between the age of grace and the age of fulfillment. The paper concludes that the church should not be driven by fear of apocalyptic events but should instead focus on faith and the empowering presence of the Holy Spirit in facing the end times with hope.